Corticosterone rapidly increases thorns of CA3 neurons via synaptic/extranuclear glucocorticoid receptor in rat hippocampus - Yoshiya, Miyuki; Komatsuzaki, Yoshimasa; Ikeda, Muneki; Hojo, Yasushi; Mukai, Hideo; Hatanaka, Yusuke; Murakami, Gen; Kawata, Mitsuhiro; Kimoto, Tetsuya; Kawato, Suguru (Frontiers in Neural Circuits, 2013)
Modulation of synapses under acute stress is attracting much attention. Exposure to acute stress induces corticosterone (CORT) secretion from the adrenal cortex, resulting in rapid increase of CORT levels in plasma and the hippocampus. We tried to test whether rapid CORT effects involve activation of essential kinases as non-genomic processes. We demonstrated rapid effects (~ 1 h) of CORT on the density of thorns, by imaging Lucifer Yellow-injected neurons in adult male rat hippocampal slices. Thorns of thorny excrescences of CA3 hippocampal neurons are post-synaptic regions whose presynaptic partners are mossy fiber terminals. The application of CORT at 100, 500 and 1000 nM induced a rapid increase in the density of thorns in the stratum lucidum of CA3 pyramidal neurons. Co-administration of RU486, an antagonist of glucocorticoid receptor (GR), abolished the effect of CORT. Blocking a single kinase, including MAPK, PKA or PKC, suppressed CORT-induced enhancement of thorn-genesis. On the other hand, GSK-3β was not involved in the signaling of thorn-genesis. Blocking AMPA receptors suppressed the CORT effect. Expression of CA3 synaptic/extranuclear GR was demonstrated by immunogold electron microscopic analysis. From these results, stress levels of CORT (100-1000 nM) might drive the rapid thorn-genesis via synaptic/extranuclear GR and multiple kinase pathways, although a role of nuclear GRs cannot be completely excluded.